An examination of athletes` mental skill, aggression and leadership levels: Turkish national wrestling teams sample - Shokoufeh, S.; Türkmen, M. (International Journal of Applied Exercise Physiology, 2020)
Purpose of this study is to analyze leadership, aggression and mental ability levels of elite male and female wrestlers in Turkey. The research sample consists of 129 athletes from four different age categories (Cadets, Juniors, U23 and Seniors) of Turkish National Wrestling Team. The scales used in this study includes; "Ottawa Mental Skills Assessment Tool (OMSAT-3)" developed by Durand-Bush, Salmela and Green-Demers (2001), validity and reliability study for Turkish language done by Erhan, Güler, Agduman and Gerek (2015); "Aggression Scale" developed by Envantery, Perry and Buss (1992), validity and reliability study for Turkish language done by Demirtas (2012); "Leadership Scale" developed by Bolman and Deal (1991), validity and reliability study for Turkish language done by Dereli (2003). Aggression Scale`s total score was normally distributed (p> 0.05). Total scores of Leadership and Mental Skills scales didn`t have a normal distribution (p <0.05). In the analysis of Aggression Scale`s total score, t-test was used for comparison of two groups and variance analysis was used for comparison of more than two groups. In the Leadership and Mental Skills scales` total score analysis, Mann-Whitney U test was used for comparison of two groups and Kruskal-Wallis H test was used for more than two groups. Statistical tests were performed using IBM SPSS (Statistical Package for the Social Sciences). Statistically significant differences were found between the sub-dimensions of Leadership, Mental Skill and Aggression. As a result of this study, we reached the conclusion that male wrestlers had higher physical aggression, transformational leadership and Competition Planning subscale scores compared to female wrestlers, and freestyle wrestlers had higher Stress Reactions, Refocusing and Fear Control subscale scores compared to Greco-Roman wrestlers.